Bourdieu on supply: utilizing the ‘theory of practice’ to understand complexity and culpability in heroin and crack cocaine user-dealing - Moyle, Leah (European journal of criminology, 2017)
The act of user-dealing has largely been explored within criminology in conjunction with the ‘drug–crime’ link or with a focus on ethnography and subculture. Whereas it is known that many users of drugs such as heroin and crack cocaine engage in small-scale supply as a way of generating revenue, less is known about the particular interplay of social context and choice that leads them to pick this income-generating activity over other potential options. Contributing to a burgeoning literature, this article explores the constrained choices of user-dealers with reference to Bourdieu’s ‘theory of practice’ (1977). Through locating stories of failure in user-dealer narratives, we utilize this novel approach in criminology, illuminating the importance of working with all of the interrelated concepts of habitus, field and capital in appreciating user-dealing as ‘practice’. It is argued that application of this framework affords the previously unharnessed opportunity to use Bourdieusian theory to understand notions of culpability when sentencing this group.